Faktor yang Memengaruhi Semangat Belajar Siswa pada Mata Pelajaran Aqidah - Tri Marfiyanto (EDUCATIO : Journal of Education, 2017)
This research aims to determine the factors that influence the motivation to learn the moral faith. This research is a qualitative study, data collection is done by conducting observations, in-depth interviews, and documentation. Data validity checks are performed by data triangulation with two modes, namely by the triangulation of the source and the triangulation technique. Data analysis is done by reducing the data, then presenting the data, then drawn conclusions. Factors that influence the motivation to learn the morality of orphans who live in the home and who live in the orphanage is the internal factor of the physiological aspect of the physical condition of the students, while the psychological aspects of which are motivation, attitude, and students ' interest in learning the moral faith. From external factors are the families in which there is habituation and economic condition of the family, as well as environmental factors and the school environment in which there are friends, and teachers